Hypocretin/Orexin and the Ventral Midbrain| Topography and Function Associated with Psychostimulant-taking and Affect - Simmons, Steven J. (Temple University, 2018)
Abuse of psychostimulants including cocaine and new synthetic formulations remains an international public health problem and economic burden. Addiction develops consequential to positive and negative drives that underlie “getting” and “staying” high. Dopamine (DA), arising from ventral tegmental area (VTA), projects to ventral striatal targets to encode reward signals and reward prediction. Mesolimbic DA is implicated in both the immediate rewarding effects of psychostimulants, and its hypoactivity underlies negative affect as drug levels decline. Accordingly, modulating inputs to midbrain DA possesses capacity to mediate positive/rewarding and negative/aversive effects of drugs. Hypocretin/orexin (hcrt/ox) is a family of excitatory hypothalamic peptides that projects widely throughout the central nervous system including to VTA DA cells, and hcrt/ox mediates brain reward function and motivation for self-administered drugs. Notably, the first-in-class hcrt/ox receptor antagonist (suvorexant) was approved for management of insomnia in the summer of 2014. Also within the past decade, the caudal division of VTA (termed “tail of VTA” and “rostromedial tegmental nucleus [RMTg]”) was detailed for its ability to negatively regulate VTA DA. Functionally, stimulation of the GABA-producing RMTg population encodes aversion and responds to aversive cues. Curiously, anatomy work depicts the hypothalamus as a principal input to the RMTg although the cellular phenotypes and functions of hypothalamic projections to RMTg have not been fully resolved. Work in this thesis was designed to map hcrt/ox projections to VTA and RMTg in effort to understand functionally-relevant topographical arrangement. In preliminary assessments, we test for the first time the ability of suvorexant to modulate reward and reinforcement associated with psychostimulant use in rats. Additionally, we profile how self-administered cocaine and “bath salt” synthetic cathinone 3,4-methylenedioxypyrovalerone (MDPV) influence affective states in rats by measuring ultrasonic vocalizations (USVs) and comparing patterns of responding. Subsequently, we test the ability of suvorexant to influence MDPV-taking and affective changes that promote self-administration. Finally, we utilize direct-site pharmacology to assess the degree to which hcrt/ox transmission within VTA and RMTg contributes to motivated responding for and affective processing of self-administered cocaine across two doses. Specifically, we hypothesized that intra-VTA suvorexant would suppress drug-taking by reducing the rewarding value of self-administered cocaine, whereas intra-RMTg hcrt/ox peptide injection would suppress drug-taking by increasing aversive value of self-administered cocaine. We observed that systemic suvorexant effectively reduces motivated cocaine-taking, and that this reduction relates in part to reductions in subjective reward of self-administered cocaine as interpreted by reductions in positively-valenced 50-kHz USVs. Retrograde tracing supports that hcrt/ox projects to both VTA and RMTg without discernible topographical arrangement. Target-site pharmacology finds that intra-VTA suvorexant has no appreciable effects on motivated cocaine-taking but tends to elevate 50-kHz USVs during the pre-drug “anticipation” time epoch in low-dose cocaine self-administering rats (0.375 mg/kg/inf). While intra-RMTg hcrt/ox pre-treatment sparsely affected USVs, 0.3 nmol/hemisphere hcrt/ox significantly enhanced cocaine-taking in low-dose cocaine self-administering rats, and, in high-dose (0.750 mg/kg/inf) cocaine self-administering rats, intra-RMTg hcrt/ox significantly suppressed responding when pre-treated with 1.0 and 3.0 nmol/hemisphere. Collectively, studies within this thesis promote the use of hcrt/ox receptor antagonists as adjunct pharmacotherapy in managing psychostimulant use disorders, although the circuitries through which aberrant motivated behaviors are modulated are not entirely clear. Future work will need to be performed to understand how hcrt/ox transmits to neurochemically-defined cell populations residing within VTA and RMTg—these pathways are recruited for processing stimuli as “rewarding” and “aversive” which are critical contributors in the development of substance use disorders and other psychiatric disorders characterized by dysregulated reward processing.